A Jewish Qur’an: An Eighteenth-Century Hebrew Qur’an Translation in Its Indian Context - Haven, Alexander van der (Religions, 2023)
This essay places the Washington Library of Congress Heb. Ms 183, a Hebrew Qur’an translation from eighteenth-century Cochin, in its South Indian context. After pointing out important general differences between early modern European and South Asian inter-religious cultures and attitudes to translation, this essay analyzes three salient differences between Ms 183 and its Dutch source. Then, the essay scrutinizes three relevant and interrelated contexts: the eighteenth-century Indian diplomatic culture of owning and exchanging scriptural translations; the social position of Muslims and Jews as ‘guests’ and diplomatic brokers; and the rise of Muslim military power in Malabar. On this basis, I argue that this Hebrew Qur’an translation was intended to be cultural–diplomatic capital for Jewish diplomats dealing with Muslim rulers, indicating that not only rulers translated the scriptures of their subjects but also subjects those of their rulers. In addition, by showing how the Mysorean rulers implemented Islamic reforms and how Jewish practices were attuned to majoritarian religious practices, the essay suggests that Ms 183 was also meant to serve Jewish religious purposes, making this manuscript possibly a rare instance of using non-Jewish religious scriptures for Jewish religious practice.